Development and Performance Evaluation of Thin-Layer Color Antiwearing Paving Materials - Zhaohui Liu; Xiangming Deng; Hao Guo; Yingchun Zhang; Di Wei; Dongmei Zhang (Advances in Civil Engineering)
To develop a color antiwearing wear layer based on epoxy resin adhesives, the effect of single formula composition on the properties of adhesives was analyzed through drawing strength tests, shear strength tests, and bending strength tests. It was found that when the mass ratio of the epoxy resin curing agent and the dosage of the toughening agent increased, the bonding performance and toughness of the adhesive firstly increased and then decreased. With the increase of the mass ratio of phenolic aldehyde amine to polyamide, the bonding performance and toughness of the adhesive were improved, but the effect was significantly reduced when the ratio was more than 2. With the increase of diluent content, the bonding performance and toughness of the adhesive were reduced. Based on response surface optimization, the optimum formulation was recommended. The content of the mass ratio of the epoxy resin to the curing agent and mass ratio of curing agent phenolic amine to polyamide, toughening agent content, and diluent content was determined to be 2.971%, 1.887%, 2.455%, and 1.000%, respectively. And, the dosage of each material was consistent with the effect of the dosage of a single formula on the properties of adhesives. The performance of the color antiwearing thin layer was tested by the adhesion test and antiwearing durability test. It was found that temperature had a significant effect on the adhesion, the adhesion of the thin layer was significantly reduced at low temperature, and the sensitivity to impact load was enhanced, while the adhesion and sensitivity to impact load were effectively improved at more than 20°C. At the same time, the antiwearing of the thin layer decreased rapidly at the initial stage under the reciprocating load but tended to be stable when the load exceeds 500 times.